2007
DOI: 10.1182/blood.v110.11.817.817
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine (AZA) Treatment Prolongs Overall Survival (OS) in Higher-Risk MDS Patients Compared with Conventional Care Regimens (CCR): Results of the AZA-001 Phase III Study.

Abstract: Background: A previous CALGB trial (JCO2002;20:2429) showed a positive OS trend with AZA vs best supportive care (BSC) in MDS. The objective of this Phase III, international, multicenter, randomized, prospective trial was to demonstrate the superiority of AZA + BSC for prolonging OS vs CCR + BSC. Design: Higher-risk MDS patients (pts), FAB-defined as RAEB, RAEB-T, or CMML (10–29% marrow blasts) with an IPSS of Int-2 or High by central pathology/cytogenetic review, were enrolled. Before randomization, investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 0 publications
2
28
1
Order By: Relevance
“…The PR 1 CR rate was 27% according to the modified IWG criteria. Although the small sample size limited our ability to draw definitive conclusions, this is similar to the PR 1 CR seen in CALGB 9221 (23%) and AZA-001 (29%), which used comparable response criteria [3,4]. The median time to best response (108 vs. 93 days) and median DOR (15 months in both) were also similar to what was reported in CALGB 9221 [3].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The PR 1 CR rate was 27% according to the modified IWG criteria. Although the small sample size limited our ability to draw definitive conclusions, this is similar to the PR 1 CR seen in CALGB 9221 (23%) and AZA-001 (29%), which used comparable response criteria [3,4]. The median time to best response (108 vs. 93 days) and median DOR (15 months in both) were also similar to what was reported in CALGB 9221 [3].…”
Section: Discussionsupporting
confidence: 72%
“…Azacitidine, a DNA hypomethylating agent, was the first drug approved by the FDA for the treatment of all FAB subtypes of MDS based on the results of CALGB 9221 [3]. Although the CALGB 9221 trial suggested an overall survival (OS) advantage for azacitidine over best supportive care (median OS 21 vs. 13 months), AZA-001 clearly demonstrated a survival advantage for azacitidine [4]. This trial enrolled patients with IPSS-High and Intermediate-2 MDS, chronic myelomonocytic leukemia (CMML) and WHO acute myelogenous leukemia (AML) (blast count 20-29%).…”
Section: Introductionmentioning
confidence: 99%
“…The reported marrow CR rates of the hypomethylating agent 5-AZA cytidine (5-AZA) are generally <10%; however, the erythroid response rate is around 50% [195]. Moreover, a preliminary reported phase III trial in 358 MDS patients with an IPSS Int-2 or High, also including RAEB-t according to the FAB classification, demonstrated 9-month longer median survival for 5-AZA treated patients compared to those receiving conventional care regimens (24 vs. 15 months respectively, P = 0.0001) [196]. The hazard ratio (HR) for survival in a multivariate analysis was 0.58 for treatment with 5-AZA versus conventional care, thus indicating a 42% lower probability of death in the 5-AZA group.…”
Section: Pharmacokinetics Of Lenalidomidementioning
confidence: 99%
“…This study reported a survival benefit. Median overall survival was 24.4 months in the 5AC arm, compared with 15 months with conventional care (P 5 0.0001; hazard ratio 0.58) and the 2-year survival was 50.8% with azacitidine, compared with 26.2% with conventional care [80].…”
Section: Dna Methyltransferase Inhibitors Azacitidinementioning
confidence: 97%